Impact of customer point verification process for the Credit Risk Management Department under the Consumer Division: a study on IDLC Finance Limited - Ullah, Kazi Tahmid (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.